EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERBASIS ETNOMATEMATIKA DAYAK BENTIAN DITINJAU DARI KEMAMPUAN LITERASI MATEMATIKA DAN SELF-EFFICACY MAHASISWA PGSD - Arifin, Nurdin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
The transition of learning from the Covid-19 pandemic to the current new normal phase provides many changes that occur and must be made. In the educational aspect, it is necessary to re-develop the ability of students, namely literacy. In addition, it is necessary to develop a sense of self-efficacy as future teachers as well as learning that applies the problems of everyday life, especially Bentian Dayak culture (ethnomathematics) with a problem-based learning model. So this study aims to find out 1) what is the Bentian Dayak ethnomathematics-based problem-based learning model is effective in terms of the mathematical literacy skills of PGSD students and 2) what is the Bentian Dayak ethnomathematics-based problem-based learning model is effective in terms of the self-efficacy of PGSD students. The research was conducted experimentally using 1) One-Shot Case Study; and 2) One-Group Pretest-Posttest Design. Based on the results of the hypothesis test conducted, it shows that; 1) The learning model with ethnomathematics-based problem-based learning is not effective in terms of the mathematical literacy skills of PGSD students; 2) The learning model with ethnomathematics-based problem based learning is effective in terms of the self-efficacy of PGSD students